POLA REKRUITMEN CALON LEGISLATIF PARTAI POLITIK - Warsito, Warsito; Prasetyo, Yeni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2006)
A political party had main function to supply for political recruitment. The recruitment processes would determine the quality and modernity of the party as well as the process of democracy. Comparing of recruitment processes of Golkar party between the general election of 1999 and 2004 was significant to identify the future of Golkar big political party as well as the next Indonesian politics. There were a lots of benefits taken from learning the recruitment.